El derecho al debido proceso de los y las estudiantes en casos de violencia en contextos educativos en la ciudad de Ibarra, período 2021-2024: Sentencia Constitucional No. 456-20-JP/21 - Bastidas Vinueza, Ana Isabel (2025)
Although education is a constitutional right, barriers persist that affect its access, quality, and enforcement, particularly regarding due process compliance in proceedings and the prevention of violence and school bullying. In response, this research focused on determining whether internal action protocols are correctly implemented based on respect for the right to due process in disciplinary procedures within the following educational institutions in the city of Ibarra: La Victoria, Pensionado Atahualpa, and Teodoro Gómez de la Torre, during the period 2021–2024. The study was based on the parameters established by Constitutional Ruling No. 456-20-JP/21: restorative justice, due process in the educational context, and codes of coexistence and action protocols. To achieve this, a mixed research approach was employed, utilizing hermeneutic and analytical methods to understand the influence of the Court's criteria on the implementation of action protocols for handling educational disciplinary procedures. The study concluded that the analyzed institutions align their actions and commission structures with the regulations issued by the Ministry of Education and Ministerial Agreement MINEDUC-MINEDUC-2023-00081-A. Furthermore, these regulations propose conflict resolution through structured ADR mechanisms that adhere to the principle of restorative justice, implemented within the respective Codes of Coexistence to apply disciplinary measures and address cases of violence occurring in the academic setting. In line with the research objective, the study evidenced that the analyzed ruling influenced the application of internal action protocols that uphold due process while respecting constitutional rights. Additionally, it highlighted the need to strengthen and train educational stakeholders in handling cases of violence to prevent and manage such conflicts effectively.